Growth Hormone Overexpression Disrupts Reproductive Status Through Actions on Leptin - Chen, Ji; Cao, Mengxi; Zhang, Aidi; Shi, Mijuan; Tao, Binbin; Li, Yongming; Wang, Yaping; Zhu, Zuoyan; Trudeau, Vance L.; Hu, Wei (Frontiers in Endocrinology, 2018)
Growth and reproduction are closely related. Growth hormone (GH)-transgenic common carp exhibit accelerated growth and delayed reproductive development, which provides an amenable model to study hormone cross-talk between the growth and reproductive axes. We analyzed the energy status and reproductive development in GH-transgenic common carp by using multi-tissue RNA sequencing, real-time-PCR, western blotting, ELISA, immunofluorescence and in vitro incubation. The expression of gys (glycogen synthase) and igfbp1 (insulin-like growth factor binding protein, as well as blood glucose concentrations are lower in GH-transgenic carp. Agrp1 (agouti-related protein 1) and sla (somatolactin a), which are related to appetite and lipid catabolism, are significantly higher in GH-transgenic carp. Low glucose content and increased appetite indicates disrupted metabolic and energy deprivation status in GH-transgenic carp. Meanwhile, the expression of such genes as gnrhr2 (gonadotropin-releasing hormone receptor 2), gthα (gonadotropin hormone, alpha polypeptide), fshβ (follicle stimulating hormone, beta polypeptide), lhβ (luteinizing hormone, beta polypeptide) in the pituitary, cyp19a1a (aromatase A) in the gonad and cyp19a1b (aromatase B) in the hypothalamus, are decreased in GH-transgenic carp. In contrast, pituitary gnih (gonadotropin inhibitory hormone), drd1 (dopamine receptor D1), drd3 (dopamine receptor D3) and drd4 (dopamine receptor 41) exhibit increased expression, which were associated with the retarded reproductive development. Leptin receptor mRNA was detected by fluorescence in situ hybridization in the pituitary including the pars intermedia and proximal pars distalis, suggesting a direct effect of leptin on LH. Recombinant carp Leptin protein was shown to stimulate pituitary gthα, fshβ, lhβ expression and ovarian germinal vesicle breakdown in vitro. In addition to neuroendocrine factors, we suggest that reduced hepatic leptin signaling to the pituitary might be part of the response to overexpression of GH and the resulting delay in puberty onset.